(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article investigates dehydration reactions of organic compounds containing two hydroxyl groups in an acidic medium. Particular attention is given to the mechanism of water elimination and the factors determining which hydroxyl group participates in the reaction. It is shown that under the influence of sulfuric acid, protonation occurs at the hydroxyl group with higher reactivity, leading to the formation of a water molecule from that group. The effect of oxygen isotopes on the reaction pathway is also discussed, indicating that hydroxyl groups containing lighter isotopes may participate more readily in dehydration processes. The obtained results are important for understanding the mechanisms of organic synthesis reactions.